Analysis Effect Of Peer Pressure On Academic Performance And Mental Health Among Students Of The Faculty Of Medicine, University Of Mulawarman, Academic Year 2024/2025 - Rakha Andhika Farras; Naufal Sulthan Al Yazid; Cecilia Florentina Sihotang; Muhammad Irfan; Amanda Amalya Putri; Galena Humairah Dahlan; Elsa Aulia Rahmawati; Grace Simanjuntak; Muhammad Arkan Ali Marwan; Raden Ayu Utami Wibowo; Khairunnida Rahma (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Students often face academic pressures that significantly affect their grades, character, and overall well-being. Peer pressure, stemming from academic demands and competition, frequently leads to comparisons with peers, influencing both academic performance and mental health. Objective : This study explores the impact of peer pressure on academic achievement and mental health among students at the Faculty of Medicine, Universitas Mulawarman, in the 2024/2025 academic year, and identifies strategies to manage it. Research Methods/ Implementation Methods : A correlational research design using quantitative methods was applied, with data collected via a Likert scale survey. The sample consisted of 69 students, with the sample size determined using the Krejcie and Morgan formula. Data were analyzed using Pearson’s correlation. Results : The results indicate a strong positive correlation between peer pressure and its negative impact on academic performance (correlation coefficient: 0.683; Interval: 0.60–0.799). Similarly, a strong positive correlation was found between peer pressure and its negative impact on students' mental health (correlation coefficient: 0.726; Interval: 0.60–0.799). Conclusion/Lesson Learned : These findings suggest that peer pressure significantly affects both academic performance and mental well-being among medical students. While the results highlight the negative aspects of peer pressure, it is important to note that peer pressure can also motivate students and improve their performance. Future research should explore both the negative and positive impacts of peer pressure in more detail.